Impact of the elimination of the donation service area on United States lung transplant practices and outcomes at high and low competition centers. Issue 12 (28th June 2020) - Drolen, Claire; Cantu, Edward; Goldberg, Hilary J.; Diamond, Joshua M.; Courtwright, Andrew
Abstract : In November 2017, the donation service area (DSA) was removed as the primary unit of US donor lung allocation. Our primary objective was to evaluate the effect of this change on recipient characteristics, the use of pretransplant extracorporeal membrane oxygenation (ECMO), and on index hospitalization length of stay (LOS) and early posttransplant complications. We also assessed whether these outcomes differed in high and low competition centers, as defined by the Herfindahl‐Hirschman Index. Following DSA removal, there was a 9‐day decrease in median waitlist time ( P = .001) and an increase in median lung allocation score (40 vs 42, P < .0001) but no difference in the need for pretransplant ECMO (incidence rate ratio = 1.16, P = .12). Median LOS increased from 17 to 19 days in the post‐DSA era ( P = .01). There was no difference in posttransplant outcomes, including prolonged ventilation, new dialysis, or early survival, in the general cohort or between competition groups. High competition centers saw an 18.5‐minute increase in ischemic time compared to low competition centers ( P = .04) but did not differentially increase single lung transplants or pretransplant ECMO utilization. Overall, DSA elimination was associated with increased posttransplant LOS but no significant differences in pretransplant ECMO or other posttransplant outcomes. Effects were largely similar at low and high competition centers. Abstract : In a retrospective cohort study comparing United States lung transplants performed in the year before versus after elimination of donation service area in the lung allocation algorithm, the authors report no effect on pretransplant resource utilization but an increase in postoperative length of stay.